Rabbitbrush along fence - Milchunas, Daniel, photographer (Colorado State University. Libraries, 2007)
Large rabbitbrush along fence on SGS with buttes in background, probably ungrazed side of fence.
Keywords: plants; grazing; SGS; shrublands; landscapes